Renal cell carcinoma with venous extension: Prediction of inferior vena cava wall invasion by MRI - Adams, Lisa C.; Ralla, Bernhard; Bender, Yi-Na Y.; Bressem, Keno; Hamm, Bernd; Busch, Jonas; Fuller, Florian; Makowski, Marcus R. (Cancer Imaging, 2018)
Background: Renal cell carcinoma (RCC) are accompanied by inferior vena cava (IVC) thrombus in up to 10% of the cases, with surgical resection remaining the only curative option. In case of IVC wall invasion, the operative procedure is more challenging and may even require IVC resection. This study aims to determine the diagnostic performance of contrast-enhanced magnetic resonance imaging (MRI) for the assessment of wall invasion by IVC thrombus in patients with RCC, validated with intraoperative findings. Methods: Data were collected on 81 patients with RCC and IVC thrombus, who received a radical nephrectomy and vena cava thrombectomy between February 2008 and November 2017. Forty eight patients met the inclusion criteria. Sensitivity and specificity as well as the positive and negative predictive values were calculated for preoperative MRI, based on the assessments of the two readers for visual wall invasion. Furthermore, a logistic regression model was used to determine if there was an association between intraoperative wall adherence and IVC diameter. Results: Complete occlusion of the IVC lumen or vessel breach could reliably assess IVC wall invasion with a sensitivity of 92.3% (95%-CI: 0.75-0.99) and a specificity of 86.4% (95%-CI: 0.65-0.97) (Fisher-test: p-value< 0.001). The positive predictive value (PPV) was 88.9% (95%-CI: 0.71-0.98) and the negative predictive value reached 90.5% (95%-CI: 0.70-0.99). There was an excellent interobserver agreement for determining IVC wall invasion with a kappa coefficient of 0.90 (95%CI: 0.79-1.00). Conclusions: The present study indicates that standard preoperative MR imaging can be used to reliably assess IVC wall invasion, evaluating morphologic features such as the complete occlusion of the IVC lumen or vessel breach. Increases in IVC diameter are associated with a higher probability of IVC wall invasion.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Inferior vena cava thrombus; Magnetic resonance imaging; Preoperative planning; Renal cell carcinoma; Sensitivity and specificity